Study on Synbiotic Beverages Based on Local Seeds and Oyster Mushrooms with the Addition of Lactobacillus casei - Siti Nurdjanah; Cherly Silvia Ericha; Suharyono Suharyono; Samsul Rizal (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Beverages are one of the most accessible liquid foods, can provide nutrients such as vitamins, minerals, antioxidants, organic acids and other bioactive substances for the body. To meet this need, the development of synbiotic drinks made from local grains is urgently needed. Synbiotic drink which is a combination of grain-based probiotics and prebiotics also has advantages for consumption for people with lactose intolerance as a substitute for dairy milk. This  study was aimed to evaluate the effect of Lactobacillus casei with various concentration on synbiotic drinks based on local grains and cereals  and oyster mushroom. Another aim from this study was to find out the best treatment for the characteristics according to SNI 7552:2018. In this study, 6 levels  formulation of L. casei concentration (0%, 2%, 3%, 4%, 5%, 6%) were used. The experiment was non-factorial and arranged in Completely Randomized Block Design with 4 replications. The data  homogeneity was tested using the Bartletts test and data additivity was tested with the Tukey test. The data were then analyzed for variance and further processed using Least Significant Difference test (LSD) at 5% level. The results showed synbiotic drink with 4% of L. casei found to be the best treatment which had a total LAB of 9.83 log CFU/mL, 0.76% lactic acid, 3.52 pH with a color score of 3.53 (rather like), a aroma score of 3.32 (neutral), a taste score of 2.34 (neutral) and an overall acceptance score of 2.83 (neutral). Keywords: Lactic acid bacteria, L. casei, Prebiotics, Probiotics, Synbiotics